Proposed upper garment design for breastfeeding women - Choi, Han Na (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This is a descriptive research that aimed to propose an ideal nursing top wear to cater the needs of nursing mothers. The study utilized 30 randomly selected breastfeeding women who participated in the survey conducted by the researcher. The respondents were divided into 2 age groups, 20 to 30 and 31 to 40 and above year olds, 15 nursing mothers per age group. The survey was conducted through a questionnaire designed by the researcher. The data gathered from the survey were tabulated and presented in tables and graphs and analyzed using simple statistical tools. The research determined that there is a lack of available stores that provide specially designed clothing for nursing women. The study also identified factors and concerns that helped the researcher in designing the proposed nursing top wear. The most common concerns identified were about functionality, fashion, comfort and privacy.